Langkah-Langkah Metode Fuzzy ELECTRE dalam Penentuan Penerima Bantuan PKH - Anthasyah, Indah Ayu Zurike; Alisah, Evawati (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2024)
Fuzzy ELECTRE is one of the methods based on the concept of outranking and comparing alternatives based on each relevant criterion. Currently, the Indonesian government has several programs as poverty alleviation, one of which is providing PKH assistance. The results of the implementation and interpretation of the fuzzy ELECTRE method using TrFN weighting to decide PKH beneficiaries. This method requires several processes, namely determining alternative decisions that are in accordance with the number of PKH beneficiaries, determining decision criteria, determining linguistic variables and giving values to each criterion based on the TrFN scale, determining the weight of the criteria based on the level of importance, determining the decision matrix, determining the normalized decision matrix, determining the weighting value on the normalized matrix entry, determining the concordance index, determining the calculation of concordance and discordance index values, determining the calculation of final concordance and discordance, and determining the ranking of the sum of the final concordance and discordance values. Thus, it can be shown that there are people who get the highest rank, namely alternatives 25,47,53,65,71,72,81,82 and 96 with a value of 184.90487 and people who get the lowest rank, namely alternative 79 with a value of -73.51765. So, this research can provide a higher level of accuracy and PKH assistance can be distributed on target.